Association of chemical and mechanical weed control methods during the pre-harvest of coffee crops - P. Ronchi,Cláudio (2020)
Abstract Background: Weed control in the pre-harvest of the coffee crop is essential to enable mechanized coffee harvesting. Objective: Testing the efficacy of pre-emergent herbicides, applied after brush shredder or desiccation operations, on the weed control during the coffee crop’s pre-harvest. Methods: Two separate trials were accomplished in commercial Coffea arabica crops in the Cerrado Mineiro Region. In the first one, oxyfluorfen and sulfentrazone were applied after either brush shredder or burndown operation; in the second, they were tested as a tank mixture with glyphosate. Results: In the first assay, the brush shredder use, associated to the rains that follow, stimulated a sharp weed infestation during the pre-harvest, which was not observed in desiccated plots. A sole application of oxyfluorfen or sulfentrazone, following either brush shedder or desiccation operation, effectively controlled the weeds; however, the sequential applications on burndown areas may be needless. The applied herbicides did not intoxicate the coffee plants nor affect their growth. In the second assay, both herbicide mixtures were highly efficient on the weed control through post-emergence application during the pre-harvest, what was not observed with a sole application of glyphosate. In both experiments, a dry period during winter, associated to the operations to gather fallen coffee fruit, collectively contributed to control weeds. Differently from oxyfluorfen, the residual effect of sulfentrazone was high enough to control weed even in the beginning of the rainy season. Conclusion: Sulfentrazone and oxyfluorfen were effective on the weed control in the pre-harvest of the coffee crop, mainly when applied after brush shedder operations.